Taṭbīq Ṭarīqah al-Tadrīb bi-Ijrā’ al-Muṭābaqah fī Ta‘allum al-Mufradāt bi al-Madrasah al-Musyaffa al-Śānawiyyah al-Islāmiyyah Semārang - Hidayah, Nailil; Inayah, Inayah; Waemamu, Waesama-ae (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to describe the application of the drill method with the Make a Match technique in vocabulary learning and analyze its effect on students' learning motivation, collaboration skills, and psychological barriers. This study employed a qualitative approach, utilizing the Classroom Action Research model designed by Kemmis and McTaggart, which was implemented in two learning cycles with class VIII students at MTs Al Musyaffa' in Semarang. Data were collected through observation using indicator sheets that assessed motivation, collaboration, and psychological barriers, and then analyzed descriptively by calculating the percentage of achievements for each cycle. The data in this study consisted of both qualitative observation data and quantitative data, specifically, students' achievement percentages in each cycle. The data sources included students, Arabic language teachers, and documentation of the learning process. Data were collected through observation sheets, field notes, and documentation of learning activities. The analysis technique employed descriptive analysis, calculating the percentage of achievement indicators for each observed aspect (motivation, collaboration, and psychological barriers) in both cycles, followed by a qualitative interpretation of the changes occurring across the cycles. The results showed a significant improvement in all three aspects observed. Students' learning motivation increased from the “sufficient” category to “excellent”. Collaboration skills showed improvement in aspects of cooperation and responsibility, while psychological barriers, such as the fear of being wrong and lack of confidence, decreased significantly. The application of the drill method, combined with the Make a Match technique, proved effective in creating a fun and interactive learning atmosphere that encouraged students' active involvement in learning Arabic.